PENGARUH EDUKASI TERHADAP PENINGKATAN KUALITAS TIDUR PADA LANSIA DENGAN HIPERTENSI DI PUSKESMAS PAMPANG - Suci Cahyaningsih Nasaru; Andi Mappanganro; Akbar Asfar; Wan Sulastri Emin (CV. Adiba Aisha Amira, 2025)
Hypertension is one of the most prevalent non-communicable diseases and remains a global health problem, often referred to as a silent killer. Elderly individuals with hypertension frequently experience poor sleep quality, which may worsen blood pressure conditions. Objective: This study aims to determine the effect of sleep quality on blood pressure in elderly patients with hypertension. This research employed a case study design on an elderly patient with hypertension at Puskesmas Pampang. The interventions provided included sleep hygiene education, restriction of coffee consumption at night, and regulation of sleep patterns. Evaluation was carried out for three consecutive days by monitoring sleep quality and measuring blood pressure. Results: Before the intervention, the patient had poor sleep quality with blood pressure levels of 167/80 mmHg and 164/85 mmHg. After the intervention, sleep quality improved, complaints of difficulty sleeping decreased, and blood pressure decreased to 162/80 mmHg. Conclusion: Improving sleep quality has an effect on reducing blood pressure in elderly patients with hypertension. Good sleep quality can serve as an important non-pharmacological factor in the management of hypertension